Prestack Parallel Modeling of Dispersive and Attenuative Medium - How-Wei Chen (Terrestrial, Atmospheric and Oceanic Sciences, 2006)

(untitled)
This study presents an efficient parallelized staggered grid pseudospectral method for 2-D viscoacoustic seismic waveform modeling that runs in a highperformance multi-processor computer and an in-house developed PC cluster. Parallel simulation permits several processors to be used for solving a single large problem with a high computation to communication ratio. Thus, parallelizing the serial scheme effectively reduces the computation time. Computational results indicate a reasonably consistent parallel performance when using different FFTs in pseudospectral computations. Meanwhile, a virtually perfect linear speedup can be achieved in a distributed- memory multi-processor environment. Effectiveness of the proposed algorithm is demonstrated using synthetic examples by simulating multiple shot gathers consistent with field coordinates. For dispersive and attenuating media, the propagating wavefield possesses the observable differences in waveform, amplitude and travel-times. The resulting effects on seismic signals, such as the decreased amplitude because of intrinsic Q and temporal shift because of physical dispersion phenomena, can be analyzed quantitatively. Anelastic effects become more visible owing to cumulative propagation effects. Field data application is presented in simulating OBS wide-angle seismic marine data for deep crustal structure study. The fine details of deep crustal velocity and attenuation structures in the survey area can be resolved by comparing simulated waveforms with observed seismograms recorded at various distances. Parallel performance is analyzed through speedup and efficiency for a variety of computing platforms. Effective parallel implementation requires numerous independent CPU intensive sub-jobs with low latency and high bandwidth inter-processor communication.